Contesting the Limits of Consultation in the Amazon Region: On Indigenous Peoples’ Demands for Free, Prior and Informed Consent in Bolivia and Peru - Delgado-Pugley, Deborah (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 2013)
While states have legal rights over more than 60% of the world’s forests, around one billion people inhabit and “manage” them often without proper legal recognition. Many countries are moving towards conferring legal rights over forested land to a broad range of private actors such as individuals or communities. However, and perhaps not surprisingly, two thirds of on-going violent conflicts involving rural communities are driven by contested claims over land and resources. In many Latin American countries, statutes and regulations on consultation have recently become strategic issues, even though these laws are suppose to comply with treaties and declarations signed by states some years or even decades before. Is it reasonable to claim that international approaches to indigenous rights, such as the ILO Convention 169 (1989) and the United Nations Declaration on the Rights of Indigenous Peoples (2007) have actually begun to influence domestic regulations in a comprehensive manner? In that sense, what is the concrete impact of these approaches in policy-making processes? Is the recognition of the right to consultation bringing improvement to environmental conditions in the jurisdictions concerned? These questions are hereby addressed by means of two case studies where laws on consultation had parliamentary approval and were promoted by State’s agencies, but were contested by indigenous peoples’ movements: the framing of the Peruvian National Law on Consultation (Law No. 29785) and the ad hoc Law on Consultation (Law No. 222) over a planned road through the Indigenous Territory and Isiboro-Sécure National Park, regarded as the basis for the Bolivian Law on Consultation.